Preparation method of low-odor spraying-free reinforced polypropylene composite material

By combining polypropylene with polytetrafluoroethylene and using catalytic adsorbent and deodorizing filter plate for multiple deodorization treatments, the problem of VOC pollution in polypropylene materials is solved, and the wear resistance and chemical stability of the material is improved. , reducing pollution and odor residue.

CN119189102APending Publication Date: 2024-12-27TIANJIN RUIJIE PLASTIC PROD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411298583.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing polypropylene materials produce high volatile organic compounds (VOCs) during processing, resulting in environmental pollution and health hazards. The existing adsorption methods such as physical adsorption and chemical adsorption have problems of low efficiency and high cost.

Method used

The preparation method of low-odor spray-free enhanced polypropylene composite material is adopted. By combining polypropylene with polytetrafluoroethylene, and dry mixing with support, nanosilicon dioxide, zeolite and other catalytic adsorbents, combined with anti-rust pigment and deodorization filter The plate was subjected to multiple deodorization treatments, and the catalytic adsorbent and extraction agent were used to reduce the odor substances.

Benefits of technology

It significantly improves the wear resistance, heat resistance and chemical stability of polypropylene, reduces the generation of harmful substances, reduces pollution, improves the yield rate, and effectively reduces the residue of odor substances through multiple deodorization treatments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119189102A_ABST
    Figure CN119189102A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of materials, and particularly relates to a preparation method of a low-odor spraying-free reinforced polypropylene composite material, which comprises the following steps: (1) premixing: adding polypropylene, polytetrafluoroethylene and a catalytic adsorbent into a mixer for dry mixing, and screening out the catalytic adsorbent to obtain a first premix; adding an auxiliary agent and a catalytic adsorbent into the mixer for dry mixing, and sieving the catalytic adsorbent to obtain a second premix; adding the anti-rust pigment into the first premix, mixing, adding the second premix, and continuously mixing to obtain a mixed material; (2) granulating: adding the mixed material and a catalytic adsorbent into an extruder, melting, filtering, extruding and granulating to obtain spray-free reinforced polypropylene composite material particles; and (3) degassing: spraying an extracting agent on the surfaces of the particles, then placing the particles on a deodorizing filter plate for standing, and finally drying the particles to obtain the low-odor spraying-free reinforced polypropylene composite material. The odor is reduced by adopting a multi-time odor removal mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a method for preparing a low-odor spray-free reinforced polypropylene composite material. Background Art

[0002] Polypropylene (PP) is widely used in various fields of people's lives due to its excellent comprehensive performance, wide sources, high quality and low price. However, affected by the polymerization process (such as catalyst, comonomer type), external auxiliary components (such as antioxidants, etc.), and processing technology (such as screw shear degree, processing temperature, etc.), the modified PP materials often have high volatile organic compounds (VOC), which pollutes the environment and harms people's health. This largely limits the application of polypropylene materials in fields with high environmental protection requirements. Therefore, the study of environmentally friendly polypropylene materials can not only expand the application field of PP but also meet the requirements of green environmental protection.

[0003] Commonly used adsorbents are divided into two categories: chemical adsorption and physical adsorption, but these two methods also have certain technical defects. Physical adsorption uses its large number of pore structures and interlayer gaps to adsorb and lock bad odors or volatile small molecules, and then seals the holes with high-viscosity fluids to achieve the purpose of reducing odors and reducing VOCs. However, the odor substances are only adsorbed and not substantially removed. When desorption conditions are met, the odor substances will also be emitted to the outside; at the same time, the adsorbent will adsorb other additives in the composite material, and the various properties of the material will be seriously negatively affected. Chemical adsorption uses chemical reactions to react with odor substances to decompose a specific type of odor substance, but a single type is more targeted and often needs to be used in combination. The deodorization efficiency is low and the raw material price is expensive. Summary of the invention

[0004] In order to solve the defect of the prior art that physical adsorption does not substantially reduce odor and VOC, the present invention provides a method for preparing a low-odor spray-free reinforced polypropylene composite material.

[0005] The technical solution adopted by the present invention is as follows: A method for preparing a low-odor spray-free reinforced polypropylene composite material comprises the following steps:

[0006] (1) Premix: adding polypropylene, polytetrafluoroethylene and a catalytic absorbent into a mixer and dry mixing them, and sieving out the catalytic absorbent to obtain a first premix; adding an auxiliary agent and a catalytic absorbent into a mixer and dry mixing them, and sieving out the catalytic absorbent to obtain a second premix;

[0007] The first premix is ​​added to the anti-rust pigment and mixed in a mixer, and then the second premix is ​​added and mixed continuously to obtain a mixed material;

[0008] (4) Granulation: adding the mixed material and the catalytic adsorbent into an extruder, extruding and granulating after melting and filtering, thereby obtaining spray-free reinforced polypropylene composite material particles;

[0009] (5) Degassing: spraying the extractant on the surface of the particles, stirring at room temperature, and then placing the particles on a deodorizing filter plate for standing, and finally placing the particles in an oven for drying to obtain a low-odor spray-free reinforced polypropylene composite material;

[0010] The catalytic adsorbent comprises a carrier, nano silicon dioxide, zeolite and nitrate, and is obtained after calcination and activation.

[0011] In one embodiment, the catalytic absorbent preparation method is as follows: add the molecular sieve carrier, nano-silica and zeolite into a nitrate aqueous solution and soak them, filter and drain them, press them into shape with a press, dry and calcine them, spray them with an alkaline solution, and heat and activate them to obtain the catalytic absorbent.

[0012] Specifically, the mass ratio of the molecular sieve carrier, nano-silica and zeolite is 100:10:15, the concentration of the nitrate aqueous solution is 1 g / L, the calcination time is 550° C., and the activation temperature is 105° C.

[0013] Furthermore, the method for preparing the deodorizing filter plate is to mix diatom mud, activated carbon, and molecular sieve in a mass ratio of 1:1:1, and add calcium oxide as a binder and water as a binder to mix and bond the materials, and then press them into plates, dry and roast them to obtain the deodorizing filter plate.

[0014] Specifically, the auxiliary agent includes a compatibilizer, a dispersant, an antioxidant and a stabilizer.

[0015] Preferably, the components are mixed in proportions by weight: 80-100 parts of polypropylene, 10-20 parts of polytetrafluoroethylene, 1-5 parts of anti-rust pigment, 1-4 parts of catalytic adsorbent, 3-6 parts of compatibilizer, 0.5-1 part of dispersant, 0.5-1 part of antioxidant, and 0.2-0.3 part of stabilizer.

[0016] Preferably, the compatibilizer is selected from maleic anhydride grafted polyethylene or EVA;

[0017] The dispersant is selected from one or more of polyethylene wax, nano-aluminum oxide, nano-titanium oxide, nano-zinc oxide, carbon black, and nano-silicon dioxide;

[0018] The antioxidant is selected from one or more of DLTP, TPP, TNP, CA, antioxidant 330, antioxidant 164, antioxidant 1010 or antioxidant 1076;

[0019] The stabilizer is selected from CPAM, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, amide-containing hindered amines, polypiperidinyl dendritic hindered amines, terminal olefin-containing hindered amines, hindered amines with a bis-hindered phenol structure, and piperidine-based N-alkoxy-substituted hindered amines;

[0020] The anti-rust pigment is selected from one or more of aluminum tripolyphosphate, red lead powder, iron red powder, composite iron titanium powder and aluminum zinc tripolyphosphate powder;

[0021] The nitrate is selected from one or more of sodium nitrate, potassium nitrate, barium nitrate, calcium nitrate, lead nitrate and cerium nitrate.

[0022] Specifically, the extractant is ethanol, acetone and water in a mass ratio of 1:1:2.

[0023] Furthermore, the extruder is set as: zone 1 180-190°C, zone 2 180-190°C, zone 3 200-210°C, zone 4 200-210°C, zone 5 200-210°C, zone 6 210-215°C, zone 7 210-215°C, zone 8 215-225°C, zone 9 215-225°C, zone 10 215-225°C, the rotation speed is 300-450rpm, the pressure is 15-20MPa, and the vacuum degree is -0.1-0.2MPa.

[0024] Beneficial effects: The present invention uses polytetrafluoroethylene in combination with polypropylene, which can not only significantly improve the wear resistance and heat resistance of polypropylene, but also enhance its chemical resistance, so that it has good chemical stability and can resist the corrosion of most acids, alkalis and organic solvents. It is more suitable for environments exposed to various chemical substances and can better allow the additives to play their role;

[0025] The use of anti-rust paint is scratch-resistant and does not fall off, which prolongs the service life and maintains the appearance; eliminating the spraying process can reduce the harmful substances produced and reduce pollution, and the parts can be recycled, which reduces the overall cost and increases the yield rate;

[0026] Multiple deodorization methods are used to reduce odor. First, blending is carried out in steps to effectively control the generation of small molecules in the processing of polypropylene. Secondly, catalytic adsorbents are added during each mixing reaction. The catalytic adsorbent uses molecular sieves as carriers. Its surface is acidic and loaded with metal ions. It can promote the flameless combustion of organic waste gas generated by the reaction at a lower temperature while adsorbing the gas, and oxidize and decompose it into carbon dioxide and water. Finally, a volatile extractant is used in combination with a deodorization filter plate to efficiently and quickly dissolve and extract residual odor small molecules on the surface, shallow layer and pores of the material, reduce internal and surface residues, and effectively improve the odor effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific implementation methods. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative changes belong to the protection scope of the present invention.

[0029] like Figure 1 As shown, the technical solution adopted by the present invention is a method for preparing a low-odor spray-free reinforced polypropylene composite material, comprising the following steps:

[0030] (1) Premix: adding polypropylene, polytetrafluoroethylene and a catalytic absorbent into a mixer and dry mixing them, and sieving out the catalytic absorbent to obtain a first premix; adding an auxiliary agent and a catalytic absorbent into a mixer and dry mixing them, and sieving out the catalytic absorbent to obtain a second premix;

[0031] The first premix is ​​added to the anti-rust pigment and mixed in a mixer, and then the second premix is ​​added and mixed continuously to obtain a mixed material;

[0032] The catalytic adsorbent comprises a carrier, nano silicon dioxide, zeolite and nitrate, and is obtained after calcination and activation.

[0033] Specifically, polypropylene, polytetrafluoroethylene and catalytic absorbent can be added to a high-speed mixer according to a ratio, dry-mixed for 5 to 10 minutes, preferably 10 minutes, and the catalytic absorbent is screened out to obtain a first premix; the auxiliary agent and the catalytic absorbent are added to the high-speed mixer according to a ratio, dry-mixed for 5 to 10 minutes, preferably 10 minutes, and the catalytic absorbent is screened out to obtain a second premix; the first premix is ​​added to the mixer and mixed at a high temperature of 105° C. for 10 minutes, then the anti-rust pigment is added and mixed for 5 to 10 minutes, preferably 10 minutes, and finally the second premix is ​​added and mixed for 5 to 10 minutes, preferably 10 minutes, to obtain a mixed material.

[0034] The preparation method of the catalytic adsorbent is as follows: add the molecular sieve carrier, nano-silica and zeolite in a mass ratio of 100:10:15 to a nitrate solution with a concentration of 1g / L and soak at room temperature for 24 hours, filter and dry, and then pressure mold to form a sphere with a particle size of 3mm, then dry and calcine at 550℃ for 2h, then spray with a 2g / L NaOH alkaline solution, heat to 105℃ for activation for 3h, and wash to obtain catalytic adsorbent particles. The catalytic adsorbent can be reused after being sieved out.

[0035] The additives include compatibilizers, dispersants, antioxidants and stabilizers. The weight ratio of each component is 80-100 parts of polypropylene, 10-20 parts of polytetrafluoroethylene, 1-5 parts of anti-rust pigment, 1-4 parts of catalytic adsorbent, 3-6 parts of compatibilizer, 0.5-1 part of dispersant, 0.5-1 part of antioxidant and 0.2-0.3 part of stabilizer.

[0036] (2) Granulation: adding the mixed material and the catalytic adsorbent into an extruder, extruding and granulating after melting and filtering, thereby obtaining spray-free reinforced polypropylene composite material particles;

[0037] Specifically, an extruder with a melt filtration function can be selected, and a filter plate can be set between the body and the head to filter out the solid particles of the catalytic adsorbent before extrusion.

[0038] (3) Degassing: spraying the extractant on the surface of the particles, stirring at room temperature, and then placing the particles on a deodorizing filter plate for standing, and finally placing the particles in an oven for drying to obtain a low-odor spray-free reinforced polypropylene composite material;

[0039] Specifically, the obtained particles are uniformly sprayed with an extractant, stirred uniformly at room temperature, spread on a deodorizing filter plate and left to stand for 1 to 2 hours, preferably 1.5 hours, and then placed in an oven at 100 to 150° C. (preferably 130° C.), nitrogen is continuously introduced, and after drying for 12 hours, a low-odor spray-free reinforced polypropylene composite material is obtained. The extractant is ethanol, acetone and water in a mass ratio of 1:1:2.

[0040] The preparation method of the deodorizing aluminum plate is as follows: diatom mud, activated carbon, and a molecular sieve carrier are mixed in a mass ratio of 1:1:1, and calcium oxide and water are added as a binder to mix and bond the materials. The materials are then pressed into a plate and evenly punched with holes. The deodorizing filter plate is obtained by drying at 100°C and calcining at 550°C.

[0041] The extruder is set as follows: zone one 180-190°C, zone two 180-190°C, zone three 200-210°C, zone four 200-210°C, zone five 200-210°C, zone six 210-215°C, zone seven 210-215°C, zone eight 215-225°C, zone nine 215-225°C, zone ten 215-225°C, rotation speed 300-450rpm, pressure 15-20MPa, vacuum degree -0.1-0.2MPa.

[0042] The compatibilizer is selected from maleic anhydride grafted polyethylene or EVA;

[0043] The dispersant is selected from one or more of polyethylene wax, nano-aluminum oxide, nano-titanium oxide, nano-zinc oxide, carbon black, and nano-silicon dioxide;

[0044] The antioxidant is selected from one or more of DLTP, TPP, TNP, CA, antioxidant 330, antioxidant 164, antioxidant 1010 or antioxidant 1076;

[0045] The stabilizer is selected from CPAM, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, amide-containing hindered amines, polypiperidinyl dendritic hindered amines, terminal olefin-containing hindered amines, hindered amines with a bis-hindered phenol structure, and piperidine-based N-alkoxy-substituted hindered amines;

[0046] The anti-rust pigment is selected from one or more of aluminum tripolyphosphate, red lead powder, iron red powder, composite iron titanium powder and aluminum zinc tripolyphosphate powder;

[0047] The nitrate is selected from one or more of sodium nitrate, potassium nitrate, barium nitrate, calcium nitrate, lead nitrate and cerium nitrate.

[0048] Example

[0049] According to the preferred mode of the above method, the composite material is prepared by using components with different component ratios, as shown in the following table:

[0050]

[0051] The obtained materials were tested for performance, and the results are as follows:

[0052] Tensile performance test: According to GB / T 1040.2-2006 standard, the tensile speed is 50mm / min;

[0053] The bending modulus and bending strength are carried out according to GB / T 9341-2008, and the bending speed is 2mm / min;

[0054] Notched impact strength is tested according to GB / T 1843-2008, and the normal temperature treatment process is 23℃ for 24 hours;

[0055] The odor test was conducted according to the German Volkswagen standard PV3900. The odor level is: not easily felt (level 1), felt but not pungent (level 2), obviously felt but not pungent (level 3), pungent (level 4), very pungent (level 5), and unbearable (level 6).

[0056] The TVOC test is carried out in accordance with the standard VDA276 of the German Association of the Automotive Industry.

[0057]

Claims

1. A method for preparing a low-odor spray-free reinforced polypropylene composite material, characterized in that: The steps include: (1) Premix: adding polypropylene, polytetrafluoroethylene and a catalytic absorbent into a mixer and dry mixing them, and sieving out the catalytic absorbent to obtain a first premix; adding an auxiliary agent and a catalytic absorbent into a mixer and dry mixing them, and sieving out the catalytic absorbent to obtain a second premix; The first premix is ​​added to the anti-rust pigment and mixed in a mixer, and then the second premix is ​​added and mixed continuously to obtain a mixed material; (2) Granulation: adding the mixed material and the catalytic adsorbent into an extruder, extruding and granulating after melting and filtering, thereby obtaining spray-free reinforced polypropylene composite material particles; (3) Degassing: spraying the extractant on the surface of the particles, stirring at room temperature, and then placing the particles on a deodorizing filter plate for standing, and finally placing the particles in an oven for drying to obtain a low-odor spray-free reinforced polypropylene composite material; The catalytic adsorbent comprises a carrier, nano silicon dioxide, zeolite and nitrate, and is obtained after calcination and activation.

2. The method for preparing the low-odor spray-free reinforced polypropylene composite material according to claim 1, characterized in that: The preparation method of the catalytic absorbent is as follows: adding molecular sieve carrier, nano silicon dioxide and zeolite into nitrate aqueous solution and soaking them, filtering and draining them, pressing them into shape with a press, drying and calcining them, spraying them with alkaline solution, and heating and activating them to obtain the catalytic absorbent.

3. The method for preparing the low-odor spray-free reinforced polypropylene composite material according to claim 2, characterized in that: The mass ratio of the molecular sieve carrier, nano-silica and zeolite is 100:10:15, the concentration of the nitrate aqueous solution is 1 g / L, the calcination time is 550° C., and the activation temperature is 105° C.

4. The method for preparing the low-odor spray-free reinforced polypropylene composite material according to claim 1, characterized in that: The method for preparing the deodorizing filter plate is as follows: diatom mud, activated carbon, and molecular sieve are mixed in a mass ratio of 1:1:1, and calcium oxide and water are added as a binder to mix and bond the materials, and then the materials are pressed into a plate, dried, and calcined to obtain the deodorizing filter plate.

5. The method for preparing the low-odor spray-free reinforced polypropylene composite material according to claim 1, characterized in that: The auxiliary agents include compatibilizers, dispersants, antioxidants and stabilizers.

6. The method for preparing the low-odor spray-free reinforced polypropylene composite material according to claim 5, characterized in that: The components are mixed in proportions by weight: 80-100 parts of polypropylene, 10-20 parts of polytetrafluoroethylene, 1-5 parts of anti-rust pigment, 1-4 parts of catalytic adsorbent, 3-6 parts of compatibilizer, 0.5-1 part of dispersant, 0.5-1 part of antioxidant and 0.2-0.3 part of stabilizer.

7. The method for preparing the low-odor spray-free reinforced polypropylene composite material according to claim 5 or 6, characterized in that: The compatibilizer is selected from maleic anhydride grafted polyethylene or EVA; The dispersant is selected from one or more of polyethylene wax, nano-aluminum oxide, nano-titanium oxide, nano-zinc oxide, carbon black, and nano-silicon dioxide; The antioxidant is selected from one or more of DLTP, TPP, TNP, CA, antioxidant 330, antioxidant 164, antioxidant 1010 or antioxidant 1076; The stabilizer is selected from CPAM, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, amide-containing hindered amines, polypiperidinyl dendritic hindered amines, terminal olefin-containing hindered amines, hindered amines with a bis-hindered phenol structure, and piperidine-based N-alkoxy-substituted hindered amines; The anti-rust pigment is selected from one or more of aluminum tripolyphosphate, red lead powder, iron red powder, composite iron titanium powder and aluminum zinc tripolyphosphate powder; The nitrate is selected from one or more of sodium nitrate, potassium nitrate, barium nitrate, calcium nitrate, lead nitrate and cerium nitrate.

8. The method for preparing the low-odor spray-free reinforced polypropylene composite material according to claim 1, characterized in that: The extractant is prepared by mixing ethanol, acetone and water in a mass ratio of 1:1:

2.

9. The method for preparing the low-odor spray-free reinforced polypropylene composite material according to claim 1, characterized in that: The extruder is set as follows: zone one 180-190°C, zone two 180-190°C, zone three 200-210°C, zone four 200-210°C, zone five 200-210°C, zone six 210-215°C, zone seven 210-215°C, zone eight 215-225°C, zone nine 215-225°C, zone ten 215-225°C, rotation speed 300-450rpm, pressure 15-20MPa, vacuum degree -0.1-0.2MPa.